2004
DOI: 10.1029/2003gl018726
|View full text |Cite
|
Sign up to set email alerts
|

A winter precipitation ‘dipole’ in the western United States associated with multidecadal ENSO variability

Abstract: The variability of winter precipitation across the western United States has important implications for a wide range of physical and socioeconomic systems. While El Niño‐Southern Oscillation (ENSO) teleconnections explain a high degree of interannual variance in western U.S. winter precipitation, their influence on decadal time scales is less well understood. In this study, we examine the relationship between ENSO conditions and winter precipitation in the western U.S. within the context of decadal‐scale varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(153 citation statements)
references
References 29 publications
6
144
0
Order By: Relevance
“…the Pacific North-west is often wet (dry) with low (high) fire activity when the South-west is dry (wet) with high (low) fire activity (Morgan et al 2001). This 'see-saw' of climatic pattern has been previously studied using rainfall and various circulation indices (Dettinger et al 1998;Brown and Comrie 2004), and now fire-scar and tree-ring networks of the western USA clearly demonstrate the importance of this phenomenon to fire regimes over multi-century periods in replicated studies (e.g. Westerling and Swetnam 2003;Schoennagel et al 2005;Kitzberger et al 2007;Heyerdahl et al 2008).…”
Section: Paleofire Climatology From Tree Rings and Fire Scarsmentioning
confidence: 68%
See 1 more Smart Citation
“…the Pacific North-west is often wet (dry) with low (high) fire activity when the South-west is dry (wet) with high (low) fire activity (Morgan et al 2001). This 'see-saw' of climatic pattern has been previously studied using rainfall and various circulation indices (Dettinger et al 1998;Brown and Comrie 2004), and now fire-scar and tree-ring networks of the western USA clearly demonstrate the importance of this phenomenon to fire regimes over multi-century periods in replicated studies (e.g. Westerling and Swetnam 2003;Schoennagel et al 2005;Kitzberger et al 2007;Heyerdahl et al 2008).…”
Section: Paleofire Climatology From Tree Rings and Fire Scarsmentioning
confidence: 68%
“…Westerling and Swetnam 2003;Schoennagel et al 2005;Kitzberger et al 2007;Heyerdahl et al 2008). The dipole has been related to the differential effect of the ENSO on the position and strength of jet streams (Dettinger et al 1998;Brown and Comrie 2004). Brown et al (2008) and Taylor et al (2008) provide further evidence and discussion of the dipole.…”
Section: Paleofire Climatology From Tree Rings and Fire Scarsmentioning
confidence: 85%
“…McCabe and Dettinger (1999) showed that the strength of western US precipitation-SOI relations closely resembles decadal variations in the PDO index. More recently, Brown and Comrie (2004) have shown inconsistencies in the canonical ENSO response in western US precipitation commensurate with the PDO phase shift. The PDO regime has also been shown to modulate winter temperature responses over most of western Canada during El Nino and La Nina events (Bonsal et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…El Niño (La Niña) events tend to bring above (below) normal precipitation to the Southwest during the winter months of December-January-FebruaryMarch (DJFM). Recent research has also shown that the stability of this teleconnection is dependent on the phase of the PDO (Gershunov and Barnett, 1998;Gutzler et al, 2002;Brown and Comrie, 2004). The negative (positive) phase of the PDO tends to bring more La Niña (El Niño) events and an extended number of years with below (above) normal winter precipitation (Gray et al, 2003).…”
Section: Connections To Southwestern Wildfire Variabilitymentioning
confidence: 99%